Thyroid Parameters and Kidney Disorder in Type 2 Diabetes: Results from the METAL Study - Yi Chen; Wen Zhang; Ningjian Wang; Yuying Wang; Chiyu Wang; Heng Wan; Yingli Lu (Journal of Diabetes Research)
Objective. Diabetic kidney disease is one of the most common microvascular complications of diabetes mellitus. We aimed to analyze the association of thyroid parameters with kidney disorders, especially in euthyroid participants. Methods. The data were obtained from a cross-sectional study, the METAL study. Thyroid parameters, including thyroid-stimulating hormone (TSH), free triiodothyronine (FT3), free thyroxine (FT4), triiodothyronine (T3), thyroxin (T4), thyroid peroxidase antibody (TPOAb), and thyroglobulin antibody (TgAb), of 4136 participants with type 2 diabetes were measured. Two structure parameters of thyroid homeostasis, including the sum activity of step-up deiodinases (SPINA-GD) and thyroid secretory capacity (SPINA-GT), and two pituitary thyrotropic function indices, including Jostel’s TSH index (TSHI) and the thyrotroph thyroid hormone resistance index (TTSI), were also calculated. Kidney disorders were described according to the presence of reduced estimated glomerular filtration rate (eGFR) and/or higher urinary albumin to creatinine ratio (UACR). Results. The prevalence of kidney disorders increased with decreasing FT3 or T3 and increasing FT4 or T4 quartile levels (all P<0.05). After full adjustment, linear regression showed that UACR levels were negatively associated with FT3 and T3 (P<0.001). In addition, eGFR was positively associated with FT3 and T3 and was negatively associated with TSH and FT4 levels and TgAb positivity (all P<0.05). By using binary logistic regression, higher TSH and FT4 and lower FT3 and T3 were associated with kidney disorders (all P<0.05). Similar results were seen in sensitivity analyses, which were performed in 3035 euthyroid diabetic participants; however, TSH was no longer related to them. The area under the receiver operating characteristic curve (AUROC) of lower FT3 for existing kidney disorder was greater than that for any other thyroid hormones (all P<0.001). The cutoff value of FT3 for reduced eGFR was 4.39 pmol/L. Regarding thyroid homeostasis parameters, SPINA-GD was negatively associated with three statuses of kidney disorders, and TSHI and TTSI were positively associated with reduced eGFR (all P<0.05). Conclusions. Among patients with type 2 diabetes, elevated TSH and FT4 (or T4), lower FT3 (or T3), TgAb positivity, lower SPINA-GD, and higher TSHI and TTSI were associated with kidney disorders. The lower FT3, even within the normal range (<4.38 pmol/L), may be the factor most related to reduced eGFR compared with other thyroid hormones in diabetic patients.